2016
DOI: 10.1016/j.jep.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and anti-inflammatory effects of Memora nodosa and allantoin in mice

Abstract: EMN have significant antinociceptive and anti-inflammatory effects, which appear to be, at least in part, due to the presence of allantoin. However, allantoin is not responsible for the EMN central antinociceptive activity. Allantoin has peripheral antinociceptive activity that involves the opioid receptor and ATP-sensitive K(+)channels. Opioid receptors are also involved in the EMN antinociceptive activity. These findings support the use of Memora nodosa in popular medicine and demonstrate that this plant has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…The beneficial effects of allantoin on inflammation, oxidative activities, and wound healing have been well known (8,9). In this study, we showed that allantoin improved gastritis, mucosal thickness, and cell numbers after ethanol-induced gastritis, decreased leukocyte, and vessel numbers and increased the PGE2 and NP-SH levels in the gastric tissue of male rats.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The beneficial effects of allantoin on inflammation, oxidative activities, and wound healing have been well known (8,9). In this study, we showed that allantoin improved gastritis, mucosal thickness, and cell numbers after ethanol-induced gastritis, decreased leukocyte, and vessel numbers and increased the PGE2 and NP-SH levels in the gastric tissue of male rats.…”
Section: Discussionsupporting
confidence: 51%
“…It has also been reported that allantoin decreases IL-4, IL-5, Ig-E levels, and the number of leukocyte cells in the ovalbumin-induced lung inflammation (11). Florentino et al (8) revealed that allantoin has anti-nociceptive and anti-inflammatory effects on the formalin-induced nociception test. Moreover, it has been shown that allantoin activates imidazoline I1-receptor (I1R) in animal and cell line studies (5,22).…”
Section: Introductionmentioning
confidence: 95%
“…The mice were placed in glass beakers and observed for 30 min. The duration of licking and biting of the paw was observed for two phases-early phase (0-5 min) and late phase (15-30 min) [23]. The percentage of licking and biting inhibition was calculated by the following formula:…”
Section: Formalin Testmentioning
confidence: 99%
“…Rats treated with allantoin at a higher dose (400 mg/kg po) exhibited improved locomotor activity and nerve velocity but the treatment had no significant effect on cold and thermal hyperalgesia, mechano‐tactile allodynia and mechanical hyperlgesia. This may be because of the peripheral antinociceptive activity of allantoin, which has been reported to involve activation of opioid receptor‐mediated ATP‐sensitive channels . Thus at a high dose (400 mg/kg) allantoin may exhibit analgesic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of circulating GLP‐1 have been found to correlate with the concentration of systemic IL‐6 and also with the concentrations of other markers of inflammation, suggesting that the regulation of GLP‐1 is inflammation dependent. It is thus worth noting that treatment with allantoin may promote the release of GLP‐1 and improve the function of β‐cells, thereby maintaining insulin and glucose levels …”
Section: Discussionmentioning
confidence: 99%